Initial engagement and persistence of health risk behaviors through adolescence: longitudinal findings from urban South Africa - Alysse J. Kowalski; O. Yaw Addo; Michael R. Kramer; Reynaldo Martorell; Shane A. Norris; Rachel N. Waford; Linda M. Richter; Aryeh D. Stein (BMC, 2021)
Abstract Background Little is known about longitudinal patterns of adolescent health risk behavior initial engagement and persistence in low- and middle-income countries. Methods Birth to Twenty Plus is a longitudinal birth cohort in Soweto-Johannesburg, South Africa. We used reports from Black African participants on cigarette smoking, alcohol, cannabis, illicit drug, and sexual activity initial engagement and adolescent pregnancy collected over 7 study visits between ages 11 and 18 y. We fit Kaplan-Meier curves to estimate behavior engagement or adolescent pregnancy, examined current behavior at age 18 y by age of first engagement, and performed a clustering analysis to identify patterns of initial engagement and their sociodemographic predictors. Results By age 13 y, cumulative incidence of smoking and alcohol engagement were each > 21%, while the cumulative incidence of other behaviors and adolescent pregnancy were < 5%. By age 18 y (15 y for cannabis), smoking, alcohol, and sexual activity engagement estimates were each > 65%, cannabis and illicit drug engagement were each > 16%; adolescent pregnancy was 31%. Rates of engagement were higher among males. Current risk behavior activity at age 18 y was generally unrelated to age of initial engagement. We identified three clusters reflecting low, moderate, and high-risk patterns of initial risk behavior engagement. One-third of males and 17% of females were assigned to the high-risk cluster. Sociodemographic factors were not associated with cluster membership. Conclusions Among urban dwelling Black South Africans, risk behavior engagement across adolescence was common and clustered into distinct patterns of initial engagement which were unrelated to the sociodemographic factors assessed. Patterns of initial risk behavior engagement may inform the timing of primary and secondary public health interventions and support integrated prevention efforts that consider multiple behaviors simultaneously.